Removal of uranium (VI) ion from aqueous solution using kaolinite - Ragiab A.M. Issa; Ayoub O. El Amari; Hana B. AlHanash; Husein M. Etmimi (Kuwait Journal of Science)
In this study, the adsorption of uranyl ion ( UO22+ ) onto kaolinite mineral from its aqueous solutions has been investigated using the batch experiment method under different parameters. Uranyl ions were measured spectrophotometrically using 8-hydroxy quinoline as a chromogen. The effect of contact time, pH, initial ion concentration, adsorbent amount, and ionic strength has been designated to establish this study. The adsorbed percentage increased dramatically as the pH increased from 1 to 5; from 28% to 70% at well-known parameters of contact time, pH value, adsorbent amount, and initial ion concentration. Above pH 5, the adsorption affinity was virtually unchanged. On the other hand, the adsorbed percentage decreased from 68% to 57% when the initial uranyl ion concentration increased from 90 to 120 ​mg/L. The overall results showed that the maximum uranyl ion adsorption percentage reached at the initial concentration of 90 ​ppm, pH 4.5, contact time of 5 ​h, and an adsorbent dosage of 4.0 ​g/L. The adsorption behavior of the uranium ion on kaolinite obeys Langmuir (1918) and Freundlich isotherm models, with R 2 value above 0.998 for both.